Overview of the central sterilization supply department, an integral part of the hospital - Brijesh Bal; Anitha Balaraju (Journal of Infection in Developing Countries)
Introduction: The central sterile supply department (CSSD) is an integrated unit in a hospital that facilitates the sterilization process. Sterilization destroys all bacteria, viruses, spores, and other microorganisms from the surface of medical devices and supplies, including fluids, which cause the spread of infection when used during patient care. This department sterilizes reusable medical devices, linen, and surgical instruments by physical or chemical methods.